2017
DOI: 10.1039/c6nr09931a
|View full text |Cite
|
Sign up to set email alerts
|

Stability, transport and ecosystem effects of graphene in water and soil environments

Abstract: Graphene nanomaterials (GMs), such as graphene oxide (GO) and reduced graphene oxide (rGO), have been widely applied in various fields. Due to the rapid increase in production and application, the inevitable release of GMs into water and soil environments poses potential health and ecosystem risks. Upon exposure, the behavior, transport, and fate of GMs may be altered after interacting with the relevant environmental conditions. GMs can affect the microbial communities as well. Thus, it is imperative to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 146 publications
0
35
1
2
Order By: Relevance
“…This could have occurred because only distilled water was used in this trial. For the remaining media, the initial absorbance of the exclusively graphene oxide suspension decreased rapidly in up to 24 h. This behavior can be explained by the fact that, because of the ionic strength of the medium, there is an increase in surface charge density and a reduction in repulsive electrostatic strength, which, as a result, causes aggregation of the material (He et al ). In the suspension of graphene oxide combined with humic acid, reductions of only 20 and 25% were observed in the initial absorbance values in ultrapure water and in L. sativa medium, respectively, after 96 h. In addition, the presence of humic acid altered the stability in the R. subcapitata , C. elegans , and Panagrolaimus sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could have occurred because only distilled water was used in this trial. For the remaining media, the initial absorbance of the exclusively graphene oxide suspension decreased rapidly in up to 24 h. This behavior can be explained by the fact that, because of the ionic strength of the medium, there is an increase in surface charge density and a reduction in repulsive electrostatic strength, which, as a result, causes aggregation of the material (He et al ). In the suspension of graphene oxide combined with humic acid, reductions of only 20 and 25% were observed in the initial absorbance values in ultrapure water and in L. sativa medium, respectively, after 96 h. In addition, the presence of humic acid altered the stability in the R. subcapitata , C. elegans , and Panagrolaimus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that the presence of humic acid can enhance the stability of graphene oxide in aquatic environments. Furthermore, it has been reported that graphene oxide can adsorb humic acid via hydrogen bonds, Lewis acid–base interactions, π–π interactions, and steric repulsions (He et al ; Clemente et al ). However, this effect was not observed in the other media examined in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that graphene materials will cause the unfavorable changes of microbial communities and biological functions in environment . Likewise, the study on microbial communities change with Ag–graphene based nanocomposites is essential for understanding their ecosystem effects. 6)Research the fate and transport of Ag–graphene nanocomposites in environment: studies on the fate and transport of AgNPs and graphene materials have been reported, which are important to evaluate their potential risks . However, the researches on the environmental behaviors of Ag–graphene based nanocomposites are limited.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Since its discovery in 2004, the number of researches on graphene has increased at an unexpected rate. Currently, the most of graphene nanomaterials used and studied are graphene oxide (GO) and reduced graphene oxide (rGO) . GO possesses abundant oxygen‐containing functional groups, which provide the possibility for further chemical modification and functionalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation